2013
DOI: 10.1007/s00228-013-1529-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of ambrisentan with clarithromycin and its modulation by polymorphic SLCO1B1

Abstract: Clarithromycin increased ambrisentan exposure to a similar extent to ketoconazole, namely, clinically minor and likely irrelevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…Before inclusion into the study, CYP2C19 alleles *2 , *3 , *4 and *17 were determined and participants were then stratified into three groups of homozygous wild‐type, poor and ultrarapid metabolizers: Extensive metabolizer group: CYP2C19*1/*1 (n = 10; wild‐type extensive metabolizer defined as absence of *2 , *3 , *4 and *17 alleles) Poor metabolizer group: CYP2C19*2/*2 (n = 4) Ultrarapid metabolizer group: CYP2C19*17/*17 (n = 6) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before inclusion into the study, CYP2C19 alleles *2 , *3 , *4 and *17 were determined and participants were then stratified into three groups of homozygous wild‐type, poor and ultrarapid metabolizers: Extensive metabolizer group: CYP2C19*1/*1 (n = 10; wild‐type extensive metabolizer defined as absence of *2 , *3 , *4 and *17 alleles) Poor metabolizer group: CYP2C19*2/*2 (n = 4) Ultrarapid metabolizer group: CYP2C19*17/*17 (n = 6) …”
Section: Methodsmentioning
confidence: 99%
“…A minor part of the drug (20%) undergoes phase I oxidative metabolism mainly by cytochrome P450 (CYP) 3A4 and to a lesser extent by the polymorphic CYPs 3A5 and 2C19 to form the pharmacologically inactive 4‐hydroxymethyl ambrisentan . Organic anion‐transporting polypeptides (OATP) partly mediate the hepatic uptake of ambrisentan, while efflux transporters do not appear to be involved in its kinetics .…”
mentioning
confidence: 99%
“…This combinatorial approach will include factors such as genetics (including rare variants), underlying disease states, and polypharmacy (drug-drug interactions) (Markert et al, 2013; Ritchie, 2012). Dr. Scott Friedman in his highlight of our recent article suggested that the confluence of multiple factors could explain some of the less common “idiosyncratic” or type B ADRs (Figure 2) (Friedman, 2014).…”
Section: Moving Forward With Precision Medicinementioning
confidence: 99%
“…The overall increase of only 33% in AUC with individual data within the ''No Effect Boundary'' indicated that no relevant clinical drug interactions were expected from subjects regardless of their CYP2D6 polymorphism, when BCQB is co-administered with paroxetine. Recent studies on drug interactions between paroxetine and aripiprazole and between clarithromycin and ambrisentan showed similar inhibition extent (30%), and found clinically minor and likely irrelevant (Azuma et al, 2012;Markert et al, 2013). Roxithromycin is known as anti-infective but also as immunomodulator, and widely used in the management and treatment of infective and/or inflammatory diseases, particularly in upper respiratory tract infections (Itkin and Menzel, 1970;Kadota et al, 1993;Plewig and Schopf, 1975).…”
Section: Discussionmentioning
confidence: 83%